Brand New Images? Implications of Instagram Photography for Place Branding - Thelander, Åsa (2017)
The aim of this article is to develop an understanding of what happens when Instagram photography is used for branding a place. Questions raised are which photographs are taken and published, does the practice result in novel ways of representing a place, and, in turn the image of a place. A practice approach to photography is used where focus is directed to the performative aspect of photography. Fifteen qualitative interviews were conducted with participants in an Instagram takeover project concerning their photographs. The study shows that adopting a communication strategy based on visual social media is dependent on the participants’ competencies and that it is embedded in everyday life. Moreover, the participants’ photographic practices were found to be influenced by social conventions, which resulted in the city being imagined differently by different participants. To use visual social media such as Instagram for branding purposes does not necessarily mean that novel images are generated, but that they are choreographed according to the conditions of Instagram as medium.